Life Cycle Ceremonies of Malayali Tribes in Jawadhi Hills – An Ethnographic Study - Ganesan, M; Thiripurasundari, P (Sakha: Multidisciplinary Journal of Science, Art & Technology, 2025)
The Malayali tribes of the Jawadhi Hills possess a rich cultural heritage reflected in their life cycle ceremonies from birth to death. This ethnographic study examines the traditional practices, beliefs, and rituals associated with different stages of life among the Malayali tribal community. The research is based on field observations, interviews with elders, and participation in community events. The study explores birth rituals such as naming ceremonies and protective customs for infants, puberty rites that signify social maturity, marriage ceremonies reflecting kinship patterns and community participation, and death rituals that reveal beliefs about ancestry and the afterlife. These ceremonies not only mark biological transitions but also reinforce social organization, cultural identity, and intergenerational continuity. The findings highlight the role of elders, customary laws, and indigenous knowledge in preserving these traditions despite external influences and modernization. The study contributes to understanding the cultural dynamics of tribal communities and emphasizes the importance of documenting and preserving indigenous practices for future generations.